Minerals, metals and sustainability : meeting future material needs - Rankin, W. J. (CSIRO Pub., 2011)
"Minerals, Metals and Sustainability examines the exploitation of minerals and mineral products and the implications for sustainability of the consumption of finite mineral resources and the wastes associated with their production and use. It provides a multi-disciplinary approach that integrates the physical and earth sciences with the social sciences, ecology and economics. Increasingly, graduates in the minerals industry and related sectors will not only require a deep technical and scientific understanding of their fields (such as geology, mining, metallurgy), but will also need a knowledge of how their industry relates to and can contribute to the transition to sustainability. Minerals, Metals and Sustainability is an important reference for students of engineering and applied science and geology; practising engineers, geologists and scientists; students of economics, social sciences and related disciplines; professionals in government service in areas such as resources, environment and sustainability; and non-technical professionals working in the minerals industry or in sectors servicing the minerals industry."--Publisher.